1993
DOI: 10.1007/bf00299326
|View full text |Cite
|
Sign up to set email alerts
|

Transcaecal ileal diversion in the management of the ?at risk? distal colonic anastomosis

Abstract: Transcaecal ileal diversion has been used in association with primary resection and anastomosis to defunction an elective distal colonic anastomosis in 10 patients and to allow on-table colonic lavage with subsequent colonic defunction in 11 patients presenting as an emergency with distal colonic obstruction. Post-operative wound sepsis occurred in four patients (19%) with a clinical anastomotic leak in one patient. The median hospital stay was 14 (10-19) days. Transcaecal ileal diversion is simple to perform.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…, in a study of intubated ileostomy, observed that defaecation began to occur after about 8 days. Transcaecal or non‐transcaecal intubated ileostomy techniques have been reported, but in the case of leakage open conversion to a conventional LI has been necessary in view of the development of faecal peritonitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, in a study of intubated ileostomy, observed that defaecation began to occur after about 8 days. Transcaecal or non‐transcaecal intubated ileostomy techniques have been reported, but in the case of leakage open conversion to a conventional LI has been necessary in view of the development of faecal peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Completely diverted tube ileostomy compared with loop ileostomy ileostomy, observed that defaecation began to occur after about 8 days. Transcaecal [5][6][7] or non-transcaecal [9,11,12] intubated ileostomy techniques have been reported, but in the case of leakage open conversion to a conventional LI has been necessary in view of the development of faecal peritonitis. The present technique used the temporary occlusion of the lumen of the distal ileum by a single line of staples to prevent early flow of faeces to the anastomotic region.…”
Section: O328mentioning
confidence: 99%
“…The studies of Yag€ ue [23] and Winslet et al [24] were conducted in 1986 and 1993, respectively, and were likely to have employed hand-sutured anastomoses. Monz on-Abad et al [25] used stapled anastomoses.…”
Section: Case Seriesmentioning
confidence: 99%
“…Yag€ ue [23] used a 24F Foley catheter with two balloons, which were inflated such that the distal balloon occluded the ileal lumen and the more proximal balloon was inflated in the caecum over the ICV, thus occluding it too. Winslet et al [24] and Monz on-Abad et al [25] used a 28F Foley catheter with a single balloon and a 26F gastrostomy tube with a single balloon, respectively, to occlude the ileal lumen at approximately 10 cm proximal to the ICV. The balloons were filled with sterile water in these instances, although radioopaque contrast was sometimes used to allow radiological control if needed postoperatively.…”
Section: Case Seriesmentioning
confidence: 99%
See 1 more Smart Citation